Modern Cognitive Competence and its Relationship to the Creative Teaching Practices of Physical Education Teachers in Salah al-Din Governorate (Texas Journal of Medical Science, 2022)
The study aimed to identify the relationship of modern cognitive efficiency with the creative teaching practices of physical education teachers in Salah Al-Din Governorate, where the research community consisted of (145) teachers of physical education. It was randomly constructed from the study population, which consisted of (100) teachers, and its validity and reliability were confirmed. And the use of the scale of creative teaching practices that was designed by (Al-Aswad, 2014) after the procedures of scientific transactions on it, and the results showed that there is no significant correlation between the modern cognitive efficiency and the creative teaching practices of physical education teachers in Salah al-Din Governorate. So, the researcher concluded the lack of physical education teachers in the governorate Salah Al-Din for the cognitive efficiency that helps them to teach and creative practices, and the researcher recommended the need for physical education teachers to keep pace with the recent developments and developments related to the concepts of cognitive efficiency in sports modernity